Autoantibodies in childhood opsoclonus-myoclonus syndrome. - Blaes, F; Pike, MG; Lang, B (2008)
Opsoclonus-myoclonus syndrome or Dancing Eye Syndrome (OMS/DES) is a rare neurological disorder of children, which associates with neuroblastoma (NB) in approximately 50% of cases. We examined sera from five patients with (OMS-NB(+)) and five without NB (OMS-NB(-)) for autoantibodies. OMS-NB(-) IgG bound to the surface of a NB cell line, whereas IgG from OMS-NB(+) and from NB patients without OMS/DES bound only to permeabilised cells. Both OMS-NB(+) and OMS-NB(-) reduced proliferation of NB cells. We also present a case report of a child with OMS/DES without NB who made a complete recovery without treatment. Serum antibodies at presentation bound to the surface and decreased NB cell proliferation but had decreased 9 weeks later when the child was asymptomatic. These results demonstrate that sera from some OMS/DES patients contain IgG antibodies that are potentially pathogenic.